A History of Smallpox Vaccination in Modern China: Vaccine Techniques, Instruments, and Localization - Jeongeun JO (Uisahak, 2023)
This paper examines how smallpox vaccination has been implemented in China from a technological perspective. It is an attempt not only to investigate the impact of technology and instruments on medical advances, but also to deepen the understanding of modern Chinese society through smallpox vaccination.Smallpox vaccination helps people develop immunity to smallpox by inoculating into them pus from cowpox which is an infectious disease that affects cows. In 1805, Alexander Pearson succeeded in smallpox vaccination using the arm-to-arm transfer method for the first time in China thanks to the arrival of the vaccine in Macao. As Pearson and Quixi, who followed in the footsteps of Pearson, used the arm-to-arm method, they did not have much interest in vaccine containers. However, the vaccine administration technique changed: the vaccine obtained from people was inoculated into cows, and then again, into people. It thus resulted in the manufacturing of various vaccine containers including glass vials and tubes. The development of tools contributed to the expansion of cowpox vaccination. In addition, cowpox vaccines were imported directly from foreign countries. Advertisements which remain to date indicate that vaccines were widely imported. Pharmacies promoted vaccines, contending that the sale and import of vaccines was for the Chinese people. On the other hand, there were voices against imported vaccines, saying that they were expensive and foreign-made. Under the banner of patriotism and nationalism, people demanded that vaccines be made in China, which led to the production of vaccines in large cities such as Shanghai and Beijing. Along with the aforementioned efforts to obtain vaccines, techniques for smallpox vaccination can also be understood in the Chinese context. For example, traditional Chinese medicine maintains that acupuncture can be used as a vaccination lancet. Since traditional Chinese medicine already embraced the use of cowpox for protection against smallpox, they advocated using acupuncture instead of western instruments in order to expand the influence of traditional Chinese medicine. The belief that inoculation should be done into acupuncture points in the upper arms shows the significant influence of traditional Chinese medicine. On the other hand, Chinese people being reluctant to leave vaccine marks show the general view of what was considered as beautiful at the time, rather than the Chinese traditional perspective.Consequently, smallpox vaccine techniques in China, while following the technological advancement in general, could not help but be adapted to the Chinese context under the influence of modern Chinese society. Thus, smallpox vaccine techniques provide clues for understanding modern Chinese society. As such, historians who conduct research mainly with literature should also take interest in medical technology and instruments as well.